MANTLE PLUMES CONTROL MAGNETIC REVERSAL FREQUENCY - Larson R.L.; Olson P. (My University, 1991)
Magnetic reversal frequency correlates inversely with mantle plume activity for the past 150 Ma, as measured by the volume production rate of oceanic plateaus, seamount chains, and continental flood basalts. This inverse correlation is especially striking during the long Cretaceous magnetic normal “superchron”, when mantle plume activity was at a maximum. We suggest that mantle plumes control magnetic reversal frequency by the following sequence of events. Mantle plumes rise from theD″ seismic layer just above the core/mantle boundary, thinningD″ to fuel the plumes. This increases core cooling by allowing heat to be conducted more rapidly across the core/mantle boundary. Outer core convective activity then increases to restore the abnormal heat loss, causing a decrease in magnetic reversal frequency in accord with model predictions for bothα2 andαω dynamos. When core convective activity increases above a critical level, a magnetic superchron results. The pulse of plume activity that caused the Cretaceous superchron resulted in a minimum increase in core heat loss of about 1200 GW over the present-day level, which corresponds to an increase in Joule heat production of about 120 GW within the core.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая